Histopathological and biomedical parameters determination in the protective effect of crocin on hepatotoxicity induced by methotrexate in rats - Cyrus Jalili; Amir Abdolmaleki; Shiva Roshankhah; Mohammad Reza Salahshoor (Shahrekord University of Medical Sciences, 2020)
Introduction: Methotrexate (Met) as a chemotherapy drug has many side effects, such as infiltration of neutrophils and the development of oxidative stress. Crocin (Cro), a carotenoid isolated from saffron, has numerous therapeutic characteristics including anticancer and antioxidant activities. This study was designed to evaluate the effects of Cro against hepatic damage in rats induced by Met. Methods: In this study, 48 male Wistar rats were randomly assigned into 8 groups, control normal (saline), Met control-treated group (20 mg/kg), Cro groups (12.5, 25, 50 mg/kg) and Met + Cro treated groups (12.5, 25, 50 mg/kg). Treatments were administered by intraperitoneal injection daily for 28 days. Griess technique was hired for the determination of serum nitrite oxide (NO) level. Concentrations of aspartate aminotransferase (AST), alanine aminotransferase (ALT), and alkaline phosphatase (ALP) were determined in order to assess liver function disturbances. In addition, Thiobarbituric acid reactive species, antioxidant capacity, the diameter of hepatocytes and central hepatic vein (CHV) were investigated. Results: Met administration significantly increased the liver malondialdehyde (MDA) and NO level, the mean diameter of CHV, hepatocytes and hepatic enzymes. Met also decreased the tissue FRAP level compared to the normal control group (P < 0.01). The Cro and Cro + Met treatments in all doses significantly reduced the mean diameter of hepatocytes and CHV, hepatic enzymes, hepatic MDA and NO levels and increased the tissue FRAP level compared to the Met control group (P < 0.01). Conclusion: It seems that the Cro administration improves liver injury induced by Met in rats.